BUSINESS CYCLES IN LATIN AMERICAN ECONOMY: 1950-2007 - Ness, Mosar Leandro; Morais, Igor Alexandre Clemente de; Massuquetti, Angélica (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
This article looks for the existence of common cycles in Latin America between 1950 and 2007. In this study, we used the technique of changing the Markovian regime, which in addition to univariate and multivariate formulations were tested bivariate arrangements. The main results indicate that it is possible to characterize the periods of growth and recessions in Argentina, Brazil, Chile and Mexico, especially in the two oil shocks in the beginning and the end of the 1970s; the crisis of balance of payments; and the problems of relative prices. Despite the existence of causality, bivariate models were tested between Argentina and Brazil, Chile and Mexico. The results suggest that smoothing of cycles, and the existence of movements of adjustment of economies to exogenous shocks that disrupted its dynamics of growth. It was also possible to identify differences in the speed of cyclical adjustment in each economy.